PENINGKATAN PRESTASI BELAJAR SISWA KELAS XI MIPA 2 MAN LUWU PADA MATERI AKHLAK TERPUJI MELALUI PENGGUNAAN POWER POINT - Hijeria . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2023)
The purpose of this study was to find out increasing students’ achievement of moral praised topic in adolescent association through the use of power point. This study used a class action research design with 2 cycles. Each cycle consists of planning, implementation, observation and evaluation, and analysis and reflection. The subjects in this study were students of class XI MIPA 2 with a total of 38 students. Data collected using test techniques. Furthermore, it was analyzed by quantitative descriptive and qualitative analysis techniques. The results of the  study show  that  the  use of  power  points  in  the  moral  praised  topic  in  adolescent association can improve student learning achievement. Keyword :  students’ achievement; power point; moral praised